Menelusuri Jejak Islam di Tanah Minahasa - Muhammad Nur Ichsan (Balai Arkeologi Provinsi Sulawesi Utara, 2018)
Entrance of Islamic religion at North Sulawesi is a development of though and for Islamic society. Islamic religion that come in early XIX and developed in the middle of XIX gave positive influence for people at North Sulawesi. The trader from Arab, China, and Netherland hostages obtained good islamization. Some area like Tondano, Bolaang-Mongondow, and Gorontalo are the illustration of success ato islamisation in Nusantara, especially at North Sulawesi. The lacal people who had opened minded as a factor of seccessed Islamasation at North Sulawesi. This article is aim to describe and find a clue of Islamization. This writing uses historical approachment and litarate method.